Six Sigma-Based Quality Assessment of Biochemical Analytes: A Comparative Analysis of Clinical Laboratory Improvement Amendments 1988 and 2024 Standards: Comparative Sigma Analysis: CLIA'88 vs CLIA'24 - Üğe, Mert; Aksun, Saliha (Journal of Medical Biochemistry, 2025)
Background: Laboratories have a responsibility to produce accurate and reliable results to ensure patient safety and meet quality standards. Within the Six Sigma quality management framework, different approaches may emerge depending on the total allowable error (TEa) limits defined by various standards. This study aimed to compare analyte sigma levels using CLIA 1988 and CLIA 2024 criteria, determine appropriate quality control procedures based on Westgard multirules, and identify potential sources of error using the Quality Goal Index.Methods: Sigma values for 17 biochemical analytes were calculated based on internal and external quality control data using the formula (TEa – bias)/CV. The Quality Goal Index (QGI) was determined using the formula bias/(1.5×CV). All analytes were evaluated at the Karabuk Public Health Laboratory between November 2024 and March 2025.Results: Amylase (Levels 1 and 2), total bilirubin (Level 1), high-density lipoprotein cholesterol (Levels 1 and 2), creatine kinase (Levels 1 and 2), and lactate dehydrogenase (Levels 1 and 2) demonstrated world-class sigma performance according to both CLIA 1988 and CLIA 2024 standards. However, a decline in sigma values was observed when calculated using the more stringent CLIA 2024 limits.Conclusions: The comparison of CLIA 1988 and CLIA 2024 standards demonstrated that stricter TEa limits can significantly impact sigma performance. While some analytes retained world-class performance, others showed a notable decline, requiring enhanced quality control measures. These findings emphasize the need for laboratories to periodically reassess test performance in light of evolving regulatory standards to ensure continued analytical reliability and patient safety.
Keywords: Six Sigma, quality tool, total allowable error, quality control,